2018
DOI: 10.1007/s12275-018-7568-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the genetic diversity and clonal population structure of Oenococcus oeni strains isolated from different wine-making regions of China

Abstract: Studies of the genetic diversity and population structure of Oenococcus oeni (O. oeni) strains from China are lacking compared to other countries and regions. In this study, amplified fragment length polymorphism (AFLP) and multilocus sequence typing (MLST) methods were used to investigate the genetic diversity and regional evolutionary patterns of 38 O. oeni strains isolated from different wine-making regions in China. The results indicated that AFLP was markedly more efficient than MLST for typing O. oeni st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…casei strains, while PFGE differentiated all the 40 strains (Cai et al, 2007 ). Likewise, in a recent study, AFLP was found to be more efficient than MLST in differentiating the Oenococcusoeni strains (Yu et al, 2018 ).…”
Section: Multilocus Sequence Typing (Mlst)mentioning
confidence: 90%
See 1 more Smart Citation
“…casei strains, while PFGE differentiated all the 40 strains (Cai et al, 2007 ). Likewise, in a recent study, AFLP was found to be more efficient than MLST in differentiating the Oenococcusoeni strains (Yu et al, 2018 ).…”
Section: Multilocus Sequence Typing (Mlst)mentioning
confidence: 90%
“…plantarum (de las Rivas et al, 2006 ; Xu et al, 2015 ), St. thermophiles (Delorme et al, 2017 ), the Lb. casei group (Bao et al, 2016 ; Diancourt et al, 2007 ; Feng et al, 2018 ), and Oenococcusoeni (De Las Rivas et al, 2004 ; Yu et al, 2018 ). Our research group used the MLST tool to differentiate the Leu.…”
Section: Multilocus Sequence Typing (Mlst)mentioning
confidence: 99%
“…plantarum (LpXJ25) and O. oeni (Oe3–31, Oe9–5, Oe144–46, Oe7–04, Oe28A-1), were isolated from different wine regions in China with great distinction of terroirs, as summarized in Table 1 . The five indigenous O. oeni strains were identified by Species-specific PCR, and their genetic diversity were analyzed by fluorescent AFLP technique in our previous work ( Yu et al, 2018 ; Yu, Shi, Meng, Liu, & He, 2019 ).…”
Section: Methodsmentioning
confidence: 99%